Quantifying the Acute Care Costs of Neonatal Bacterial Sepsis and Meningitis in Mozambique and South Africa. (2nd November 2021) - Aerts, Céline; Leahy, Shannon; Mucasse, Humberto; Lala, Sanjay; Bramugy, Justina; Tann, Cally J; Madhi, Shabir A; Bardají, Azucena; Bassat, Quique; Dangor, Ziyaad; Lawn, Joy E; Jit, Mark; et al.
Abstract: Background: Sepsis and meningitis are among the leading causes of neonatal deaths in sub-Saharan Africa (SSA). Neonatal sepsis caused ~400 000 deaths globally in 2015, half occurring in Africa. Despite this, there are few published data on the acute costs of neonatal sepsis or meningitis, with none in SSA. Methods: We enrolled neonates admitted to 2 hospitals in South Africa and Mozambique between 16 April 2020 and 1 April 2021. In South Africa all cases were microbiologically confirmed, but in Mozambique both clinically suspected and microbiologically confirmed cases were included. Data were collected on healthcare resource use and length of stay, along with information on household expenditure and caregiving. We used unit costs of healthcare resources in local currencies to estimate healthcare provider costs per patient and costs per household. Results were converted to 2019 international dollars (I$). Results: We enrolled 11 neonates in Mozambique and 18 neonates in South Africa. Mean length of stay was 10 days (median, 9 [interquartile range IQR, 4–14) and 16 days (median, 15 [IQR, 13–18]), respectively. In Mozambique we estimated mean household costs of I$49.62 (median, 10.19 [IQR, 5.10–95.12]) and hospitalization costs of I$307.58 (median, 275.12 [IQR, 149.43–386.12]). In South Africa these costs were I$52.31 (median, 30.82 [IQR, 19.25–73.08]) and I$684.06 (median, 653.62 [IQR, 543.33–827.53]), respectively. Conclusions: We found substantial costs associated with acute neonatal bacterial (all-cause) sepsis and meningitis in SSA. Our estimates will inform economic evaluations of interventions to prevent neonatal invasive bacterial infections.